Assessing a quality model for the social sector: an empirical study of the EQUASS model. (2nd January 2019) - Melão, Nuno; Bastida, Ramon; Marimon, Frederic
Abstract : Although the recent publication of a few scholarly papers has contributed to shorten the research-practice gap, there is still a shortage of empirical studies on quality management (QM) in the social sector. In particular, the study of the causal relationships incorporated in quality models that are specifically tailored to this sector remains to be examined. This research addresses this gap by (i) empirically analysing the fitness of the model underlying European Quality in Social Services (EQUASS), a QM and excellence programme for European social services, and (ii) proposing a model with an improved fit. It uses a structural equation modelling approach on a sample of 339 external audits from 32 European organisations that were awarded an EQUASS recognition or certification between 2012 and 2015. Results reveal that the EQUASS model (2012 version) does not fit with the sample collected. An improved model with seven constructs is proposed, which shows excellent psychometric properties and good fit indexes. This research provides a better understanding of the causal relationships between QM practices embedded in the EQUASS model, along with a simpler alternative model that is especially suited to small- and medium-sized providers, which represent the majority of the organisations in the social sector.